Space Technology Advances Application in Town Planning - Babayeva, Nargiz A.; Amenzade, Rayxa B.; Rustamov, Rustam B. (Journal of Environmental Science and Engineering Technology, 2014)
This paper is dedicated space technology advances use architectural design in town planning for selected area of Gobustan district, Azerbaijan. It describes conceptual approach of the process of use space technology in initial stages of design process. This paper briefly observes an option of remote sensing platform for data collection with further geographical information system (GIS) technology applications. The decision oriented on the importance of linking remote sensing systems with GIS. The use of GIS is contained in application such as image classification, calibration and environmental modeling. There is clearly great complimentarily between remote sensing and GIS. Existing remote sensing method and GIS technology are operating and functioning independently. It is necessary to mention that by linking the technology, concepts and theories of remote sensing into GIS, information systems considerable richer and more sophisticated can be created for use in substantive applications. The fact is that application indicated technology for collection necessary data during execution and decision making of engineering solutions. An advantage of use of space technology is an excellent instrument of merging and integration accessed data into geographical coordination stimulated of easily those definition and importance in all the stage of engineering executions.